Religion and the Polls: Strengthening Nigeria’s Democracy through the Separation of Religion and Politics - Hussaini Said Yusuf; Mathew Stephen; Lydia Daniel; Usman Sa’ad (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2026)
The intersection of religion and politics remains one of the most critical challenges to Nigeria’s democratic consolidation. Although the constitution upholds secularism, political actors continue to exploit religious sentiment for electoral gain. This paper explores how maintaining a clear separation between religion and politics can promote inclusivity, peace, and effective governance in Nigeria. Guided by Social Conflict Theory and Secularization Theory, the study adopts a qualitative method using secondary data from academic and institutional sources. The findings indicate that faith-based mobilization during elections undermines accountability, deepens voter polarization, and obstructs national cohesion. The paper advocates for secular governance, civic education, and institutional reforms that reinforce faith neutrality in political processes. Strengthening democracy in Nigeria, it argues, requires leaders and citizens alike to prioritize competence, integrity, and the common good over sectarian loyalty.